Awareness and Perceived Instructional Usefulness of Arabic Language Application Software among Junior Secondary School Students - Sanusi, Taofeeq Olamilekan; Hameed Olalekan Bolaji (Universitas Pendidikan Ganesha, 2024)
Language teachers need to see technology as an instrument that can make language teaching and learning better. However, the usefulness of application software in the actual teaching and learning process of learning a specific language, such as Arabic, remains unexplored. This study aims to analyze the awareness and perceived instructional usefulness of Arabic language application software among junior secondary school students. This study adopted a descriptive survey type, the population for this study included all junior secondary schools. The purposive sampling technique was used to select 240 junior secondary school students. The data gathered were analyzed using the Pearson Product Moment Correlation (PPMC). T-test was used to test the difference between variables in hypothesis one and Analysis of Variance (ANOVA) was used to test the difference among variables in null hypothesis two at 0.05 level of significance. The study found that there is a significant difference in the level of awareness of Arabic language application software among junior secondary school students on the basis of gender (F.cal. = 3.20 > tvalue= 1.96). The study discovered that there is a significant difference in the perceived instructional usefulness of Arabic language application software among junior secondary schools’ students on the basis of class level (F-cal 2.41 > Tvalue 1.96). It was concluded that there is a significant difference in the level of awareness of male and female students on the Arabic language application software for learning of Arabic language among junior secondary schools’ students.